1995
DOI: 10.1177/153857449502900107
|View full text |Cite
|
Sign up to set email alerts
|

Cor Triatriatum Dexter Echocardiographic Diagnosis and Successful Surgical Correction in an Infant

Abstract: Cor triatriatum dexter is a very rare cardiac malformation in which the right atrium is subdivided into two distinct chambers. The authors report the case of a three-day-old infant boy with body weight of 2.8 kg, severely symptomatic, with highly obstructive cor triatriatum dexter and patent foramen ovale. The malformation was diagnosed by twodimensional echocardiography and corrected successfully by surgery. 49 From the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In a majority of cases, the right atrial membrane was reportedly found at the operating table or upon autopsy 1 . It is important to recognise on time cor triatriatum dexter as it is amenable to simple surgical correction with resection of the right atrial membrane and closure of the atrial septal defect 9 . In some cases, owing to high surgical risk, percutaneous balloon dilation of the obstructive membrane may be considered to relieve the atrial obstruction 10 …”
Section: Discussionmentioning
confidence: 99%
“…In a majority of cases, the right atrial membrane was reportedly found at the operating table or upon autopsy 1 . It is important to recognise on time cor triatriatum dexter as it is amenable to simple surgical correction with resection of the right atrial membrane and closure of the atrial septal defect 9 . In some cases, owing to high surgical risk, percutaneous balloon dilation of the obstructive membrane may be considered to relieve the atrial obstruction 10 …”
Section: Discussionmentioning
confidence: 99%